Fe controls the reproduction of zoogloea and sludge bulking in oil-in-iron wastewater - Shi, Xinfeng; Su, Zhibin; Tao, Xiaoxia; Zhou, Xin; Zhao, Jinbo; Wang, Ruiqi; Qin, Jinyi (Frontiers in Water, 2023)
Following the final biological treatment, the oil wastewater is intended for reuse in factory floor cleaning. However, the presence of varying concentrations of oil-in-iron characteristic wastewater has led to a sudden surge in sludge SV to 90% , adversely affecting water treatment efficiency. In this study, we conducted an analysis of microbial community structure and selected pepA and 16S rRNA primers to assess the proportions of zoogloea and total bacteria in sludge bulking. Iron concentration plays a pivotal role, and it should be maintained at or 0.6 mgL-1. By selective discharging of sludge to maintain 1700 mgL-1 , we minimized iron enrichment, thereby enhancing the sludge settling performance. Maintaining dissolved oxygen (DO) at 3.5 mgL-1 supports the aerobic sludge's ability to replenish iron in its system, while the oil content should be controlled at 145.33 mgL-1 to reduce the release of iron into the water. The order of significance is as follows: sludge concentration > Fe amount > DO > oil content. Implementing this approach was applied in the field for one week and effectively reduced the SV from 90% to approximately 43%. The interaction between quorum sensing molecules related to sludge bulking and iron, leading to the formation of complexes, underscores the significance of controlling iron levels. This study offers a valuable case for practical application of quorum quenching technology in oil wastewater, presenting a rapid, efficient, and cost-effective solution to address the issue of sludge bulking.